SOIL NUTRITION MANAGEMENT AND PREDATION BY CHEILOMENES SEXMACULATA (COLEOPTERA: COCCINELLIDAE) IMPACTS ON APHIS GLYCINES (HOMOPTERA: APHIDIDAE) - Rosma Hasibuan & Jamalam Lumbanraja . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2010)
Soil nutrition management and predation by Cheilomenes sexmaculata (Coleoptera: Coccinellidae) impacts on Aphis glycines (Homoptera: Aphididae). Understanding how soil nutrient availability and natural enemies impacts on aphid populations are important for soybean aphid, Aphis glycines Matsumura (Homoptera: Aphididae), management. Studies were conducted to examine the effect of soil nutrient management and predaceous coccinellid beetle, Cheilomenes sexmaculata (Fabr.), (Coleoptera: Coccinellidae) on A. glycines population. The plot size of 300 m2 was set up into 12 plots consisting four treatments and three replications. The treatments were the combination of NPK (urea 100 kg ha-1 + SP-36 200 kg ha-1 + KCl 200 kg ha-1) levels, dolomite (4 ton ha-1), compost (10 ton ha-1), and chicken manure (10 ton ha-1). While, the predator’s potential of C. sexmaculata was measured both in the field and laboratory conditions. The results of the studies indicated that soil nutrition treatments had significant effects on the plant performances: leaf numbers; pod numbers; and plant height. In line with this result, there were significant effects of soil nutrient treatments on the amount of plant nutrient: C, N, P, K, C, Ca, and Mg. The positive correlation coefficient was observed between the aphid population and nitrogen content, while the significant negative correlation found on between aphid population and the calcium and magnesium content. Meanwhile, the mean number of soybean aphids (A. glycines) consumed by C. sexmaculata increased from 8.915 to 40.64 aphids, with an average 26.35 ± 3.16 aphids. The mean numbers of aphids consumed by predator were significantly influenced by prey densities. The exclosure study result showed that the densities of A. glycines in caged plants was higher than that in un-caged plants. In the no-cage treatments, natural enemies had complete access to soybean aphids and caused the total reduction (100%) of A. glycines density by the 8th wk sample period. These findings suggest that reducing the amount of synthetic chemical fertilizer NPK can be supplemented with natural organic materials such as composts and chicken manure and natural occurring predator, C. sexmaculata, is an important natural enemy of the soybean aphid.